Energy Gel : a new product introduction (A) - Raviv, Artur; Henrich, Jan M.; Steinroeder, Gero K. (London : SAGE Publications Ltd, 2017)
Presents an analysis of the decision regarding a new product introduction. The main issues for discussion are: sunk costs, incremental costs, cannibalization, shared facilities, and the treatment of inflation.
Originally published: Raviv, A., Henrich, J. M., & Steinroeder, G. K. (2003). Energy Gel: A New Product Introduction (A). 5-403-756(A) Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; New products -- Management -- Case studies; Product management -- Case studies; Fatigue -- Prevention -- Case studies